Increased risk of stroke in contact dermatitis patients: A nationwide population-based retrospective cohort study. Issue 10 (March 2017) - Chang, Wei-Lun; Hsu, Min-Hsien; Lin, Cheng-Li; Chan, Po-Chi; Chang, Ko-Shih; Lee, Ching-Hsiao; Hsu, Chung-Yi; Tsai, Min-Tein; Yeh, Chung-Hsin; Sung, Fung-Chang
Abstract : Abstract: Dermatologic diseases are not traditional risk factors of stroke, but recent studies show atopic dermatitis, psoriasis, and bullous skin disease may increase the risk of stroke and other cardiovascular diseases. No previous studies have focused on the association between contact dermatitis and stroke. We established a cohort comprised of 48, 169 contact dermatitis patients newly diagnosed in 2000–2003 and 96, 338 randomly selected subjects without the disorder, frequency matched by sex, age, and diagnosis year, as the comparison cohort. None of them had a history of stroke. Stroke incidence was assessed by the end of 2011 for both cohorts. The incidence stroke was 1.1-fold higher in the contact dermatitis cohort than in the comparison cohort (5.93 vs 5.37 per 1000 person-years, P < 0.01). The multivariable Cox method analyzed adjusted hazard ratios (aHRs) were 1.12 (95% confidence interval [CI], 1.05–1.19) for all stroke types and 1.12 (95% CI, 1.05–1.20) for ischemic stroke and 1.11 (95% CI, 0.94–1.30) for hemorrhagic stroke. The age-specific aHR of stroke for contact dermatitis cohort increased with age, from 1.14 (95% CI, 1.03–1.27) for 65 to 74 years; to 1.27 (95% CI, 1.15–1.42) for 75 years and older. The aHR of stroke were 1.16 (95% CI, 1.07–1.27) and 1.09 (95% CI, 1.00–1.18) for men and women, respectively. This study suggests that patients with contact dermatitis were at a modestly increased risk of stroke, significant for ischemic stroke but not for hemorrhagic stroke. Comorbidity, particularly hypertension, increased the hazard of stroke further.